Voter Behaviour and The Campaign Pattern of Candidates during Pandemics in Regional Head Election in Medan City, North Sumatra - Fauzan, Indra (Politika: Jurnal Ilmu Politik, 2022)
Covid-19 has influenced the process of democracy in many countries, including Indonesia, especially in the local election. The political campaign involving mass mobilisation was restricted, so the candidates were encouraged to use online media to reduce the Covid-19 spread. Based on this problem, this study aims to analyse the campaign patterns between candidates in a regional head election in Medan during a pandemic and how the candidates increase voter turnout. This study used both the qualitative method by interviewing the campaign team of the candidates in charge of online and offline media and the quantitative method by distributing the questionnaires to measure the behaviour of the voters. This study showed that the perception of popularity and electability influenced the pattern of candidate campaigns, and the low political awareness of the community influenced low participation in political campaigns and voter turnout, besides unhealthy campaigns and negative perception of local government. Therefore, although face-to-face was restricted, the candidates believed that direct meetings with the voters were only the way to influence the voter and increase political participation.